Paraquat Herbicide in Peat Soil: I. Its Effects on the Dynamics of Microbial Population - Sebastian Margino; Erni Martani; Bambang Hendro Sunarminto (Universitas Gadjah Mada, 2000)
Paraquat has been used widely and periodically in peat soil. It is stable in acid environments, therefore its application in peat soil which represents an acid environment, might prolong its persistence. Liming treatment has known to reduce peat soil acidity. This research was conducted to study the effect of paraquat and liming treatments on the dynamics of microbial population in peat soil. Unlimed and limed peat soil were treated with paraquat to a final concentration of 20 ppm, and incubated for 2 months. Microbiological analysis, consisting of counting of bacterial, actinomycetes, and fungal population were done weekly. The changes of pH value and paraquat residue were also measured. The results showed that in unlimed peat soil, paraquat treatment did not influence microbial population. However, when paraquat was added into limed peat soil, the number of microbial population decreased; especially the population of bacteria. Liming treatment increased bacterial population and changed the population dynamics of actinomycetes. No significant difference of fungal population in peat soil treated with paraquat and lime. Additionally, there was no significant difference in paraquat resistance between limed and unlimed peat soil.